BINJAI CITY GOVERNMENT POLICY ON PROVIDING ASSISTIVE TOOLS FOR PEOPLE WITH DISABILITIES AT THE BINJAI CITY SOCIAL SERVICES REVIEWED FROM THE PERSPECTIVE OF FIQH SYASAH - Tiara Dyah Wira Ningsih; Maulidya Mora Matondang (Program Pascasarjana UIN Sumatera Utara, 2026)
This study analyzes the Binjai City Government's policy on providing assistive devices for people with disabilities through the Binjai City Social Service and reviews it from a fiqh siyasah perspective. The study uses a normative-empirical legal approach with data collection techniques through literature studies, observation, documentation, and interviews with relevant parties at the Binjai City Social Service. The results show that the policy on providing assistive devices has been implemented in the form of social assistance such as wheelchairs, canes for the blind, hearing aids, and other supporting devices according to the needs of beneficiaries. Empirical findings indicate that this program contributes to increasing mobility, independence, and social access for people with disabilities. However, its implementation has not been fully optimal due to budget constraints, incomplete recipient data collection, and uneven distribution of assistance. From a fiqh siyasah perspective, this policy is in line with the principles of maslahah, justice, government mandate, and protection of vulnerable groups. The scientific contribution of this study lies in strengthening the study of inclusive social policies based on Islamic governance values, particularly in fulfilling the rights of people with disabilities at the local government level.